2023
DOI: 10.3390/nano13071241
|View full text |Cite
|
Sign up to set email alerts
|

Co3O4 Supported on Graphene-like Carbon by One-Step Calcination of Cobalt Phthalocyanine for Efficient Oxygen Reduction Reaction under Alkaline Medium

Abstract: Exploiting cost-effective and durable non-platinum electrocatalysts for oxygen reduction reaction (ORR) is of great significance for the development of abundant renewable energy conversion and storage technologies. Herein, a series of Co3O4 supported on graphene-like carbon (Co3O4/C) samples were firstly effectively synthesized by one-step calcination of cobalt phthalocyanine and their electrocatalytic performances were measured for ORR under an alkaline medium. By systematically adjusting the calcination temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…It could be demonstrated that K 2 CO 3 and CaCO 3 were generated during charge–discharge cycling [ 7 , 8 , 11 , 26 , 27 , 28 , 37 ]. Considering the voltage loss (i.e., iR drop) caused by the electrolyte solution between the working electrode and the reference electrode, corrected ORR and OER performance of the cycled air cathode by iR compensation was investigated in Figure 8 , and both of them were significantly decreased after cycling, and its performance with a modified electrolyte deteriorated more than the one with a modified separator [ 8 , 11 , 26 , 27 , 28 , 29 , 30 , 49 , 50 ]. After cycling, the micropores of the air cathode could easily be blocked by the generated lamellar K 2 CO 3 , hindering the diffusion of O 2 through the air cathode to participate in ORR and OER reaction, resulting in the remarkable decrease in ORR and OER performance of air cathode.…”
Section: Resultsmentioning
confidence: 99%
“…It could be demonstrated that K 2 CO 3 and CaCO 3 were generated during charge–discharge cycling [ 7 , 8 , 11 , 26 , 27 , 28 , 37 ]. Considering the voltage loss (i.e., iR drop) caused by the electrolyte solution between the working electrode and the reference electrode, corrected ORR and OER performance of the cycled air cathode by iR compensation was investigated in Figure 8 , and both of them were significantly decreased after cycling, and its performance with a modified electrolyte deteriorated more than the one with a modified separator [ 8 , 11 , 26 , 27 , 28 , 29 , 30 , 49 , 50 ]. After cycling, the micropores of the air cathode could easily be blocked by the generated lamellar K 2 CO 3 , hindering the diffusion of O 2 through the air cathode to participate in ORR and OER reaction, resulting in the remarkable decrease in ORR and OER performance of air cathode.…”
Section: Resultsmentioning
confidence: 99%
“…Pre-synthesized porous networks, such as metal-organic frameworks (MOFs) are oen utilised precursors with the choice of enriched metal centres and ligand/linker carbon network with functional heteroatom groups, which can enhance the electrophilicity and heterogeneity of the metalcarbon network and thus promote the adsorption/desorption of reactants/intermediates during the catalytic process. 1,[3][4][5][6][7][8][9][10][11][12][13][14][15]18,[22][23][24] MOFs, such as ZIFs comprising highly accessible porosity and surface area along with metal and nitrogen elements have delivered superior functional electrocatalysts in the form of metal-nitrogen-carbon (usually denoted as M-N-C) or metal/ metal-oxide nanoparticle embedded N-C matrix (MO x -N-C or M@MO x -N-C). For example, the carbothermal modulation of Co metal based MOFs/ZIFs can generate Co-N-C or Co@Co 3 O 4 and/or Co@CoO x nanoparticles embedded N-C materials.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the carbothermal modulation of Co metal based MOFs/ZIFs can generate Co-N-C or Co@Co 3 O 4 and/or Co@CoO x nanoparticles embedded N-C materials. [3][4][5]7,[10][11][12][13]15,18,22,23,[27][28][29][30][31][32][33][34][35][36] However, the high-temperature carbothermal modication process, commonly carried out between 800-1000 °C for a few hours, along with signicant ligand volatility and metal-centres agglomeration, limits their full potential of scalable synthesis and efficient electrocatalytic performance. Attempts to use low-temperature carbothermal synthesis resulted in unsatisfactory electrochemical performance due to poor electrical conductivity of carbon network.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations